Awake pancreaticoduodenectomy without intubation: exploring short-term clinicopathological outcomes of epidural vs. general anesthesia - Hassan, Iyad; Hassan, Lina; Gamal, Ibrahim; Ibrahim, Mohamad; Hassan, Wiam (Frontiers in Surgery, 2025)
BackgroundThere is some evidence to suggest that general anesthesia may influence oncological outcomes, such as survival and disease-free recurrence, in addition to surgical outcomes. This study compares the clinico-oncological outcomes of pancreatic cancer patients who had a pyloric-preserving pancreaticoduodenectomy (PPPD) under epidural anesthesia without endotracheal intubation (EA) and those who received general anesthesia (GA).MethodsA retrospective cohort investigation comparing pancreatic cancer patients with PPPD under GA and EA. The procedure's feasibility and 30-day clinico-pathological outcomes were evaluated between groups.ResultsThe ratio of males to females was 16:5. The mean age was 51 years (range 27–74 years). The median hospital stay was 12 days (range 7–60). In the GA group, thirteen patients had PPPD and one patient received total pancreatectomy with splenectomy (TPS). On the other hand, in the EA group, six patients received PPPD and two patients underwent TPS. The two groups had similar preoperative demographics, including ASA classification. Seven EA patients underwent successful surgery without GA conversion. Due to respiratory acidosis, one TPS patient was converted to GA before abdominal closure. Neither group had mortality or major cardio-pulmonary issues, with the exception of one case in the GA group who acquired COVID-19 while hospitalized and was ventilated for 10 days until completely recovering. Surgical complications occurred as follows: Two GA patients had pancreatic fistula type B, and one EA patient had a biliary leak, both treated conservatively. One GA patient needed a revision laparoscopy after an iatrogenic bowl perforation during IR drain insertion for chylous ascites on postoperative day 30. All cases had an R0 resection. The histological tumor stage was similar in both groups. The EA group had significantly more harvested lymph nodes and a higher number of lymph node metastases (p = 0.022 and P = 0.005, respectively).ConclusionsPancreaticoduodenectomy with just epidural anesthesia and without endotracheal intubation can be performed safely in selected cases. It may decrease surgical complications without affecting oncological outcomes. Additional research is necessary to comprehend its actual advantages.